Anterior tibial artery perforator plus flaps: Role in coverage of posttumor excision defects around the knee joint and upper leg - Harshvardhan Sahijwani; Vikas Warikoo; Abhijeet Ashok Salunke; Jaymin Shah; Preetish Bhavsar; Rahul Wagh; Subodh Pathak (Elsevier, 2017)
Objective: Posttumor excision defects can be very large, and many do require postoperative radiotherapy. It is therefore important to provide stable and durable wound coverage to provide ability to withstand radiotherapy as well as providing cover to vital structures. Methods: Between July 2014 and June 2016, eight females and six male patients with defects around the knee were operated upon using a perforator plus flap from the anterior tibial artery perforator. In all except two patients, the defects were the result of posttumor extirpation, while in the latter, it was due to impending implant exposure following bone tumor excision and tibial prosthesis. A constant perforator at the neck of the fibula was found using hand-held Doppler. The base of the flap was always kept intact. The flap was then transposed toward the defect and inset in a tensionless manner. Results: The average flap dimension was 14 cm × 5.5 cm. The mean follow-up was 11 months (6-20 months). All the flaps survived well except in one patient who developed partial tip necrosis, providing stable coverage of the wound. Two patients developed local recurrence and had to undergo above-knee amputation. Conclusions: The planning for the reconstruction of defects following tumor resection is to be done in accordance with a multidisciplinary team approach involving oncosurgeon, reconstructive plastic surgeons, and radiation specialist. The perforator plus flap is an excellent choice in defects around the knee to cover neurovascular structures, bone, or implant.